Soil fauna responses to land-use change are size-dependent and linked to soil compaction and organic matter - Pérez Roig, Camila (2026)
The conversion of natural ecosystems into agricultural land is a major driver of biodiversity loss globally. However, the effects on soil fauna are often unclear due the divergent responses among size classes, the influence of local conditions, and the use of broad land-use categories. Furthermore, the covariation of soil fauna and soil properties is rarely reported in the literature. Here, we assessed soil fauna in north-Patagonian forests across multiple land uses on six farms, including reference native forests, to evaluate changes across mesofauna, macroarthropods, and earthworms. We also evaluated community composition shifts and their covariation with key soil properties. Land use significantly affected soil fauna metrics, with differential effects across size classes. While cattle grazing had no significant effects, sheep grazing and seasonal crops led to significant declines in mesofauna density and macroarthropod density, biomass, and richness (up to 65 %). Conversely, these same systems showed increased earthworm density, biomass, and richness (up to 2.8-fold). Perennial crops supported higher macroarthropod and earthworm richness (40–70 %). Land use also drove increasing shifts in community composition across size classes. Bulk density and particulate organic matter contributed the most to the covariation between soil fauna and physicochemical properties for all size classes. Our findings demonstrate that land uses most detrimental to macroarthropods were the most beneficial to non-native earthworms. Additionally, they suggest that reducing sheep stocking rates is crucial to mitigate soil biodiversity loss in this region, while well-managed cattle grazing and perennial crops represent viable strategies to integrate food production and soil biodiversity conservation.